Cell-based internal standard for qPCR determinations of antibiotic resistance indicators in environmental water samples - Rocha, Jaqueline (2020)
Quantitative PCR (qPCR) has been used to quantify antibiotic resistance genes (ARGs) in water, wastewater, soil, sediment and tissue samples. Concerns regarding the comparability of data obtained in different laboratories has been a major bottleneck to incentivize the compilation of publicly available of ARGs quantifications gathered from different reports. In this study, the influence of the DNA extraction kits (NZY Tissue gDNA Isolation kit or DNeasy PowerWater kit) and of the operator on the DNA extraction yield and on qPCR genes quantification was assessed. Since in wastewater and water samples the matrix effect can affect the DNA recovery and, therefore, gene quantification, an internal standard, consisting in a cloned gene not found in environmental samples, was tested. The aim was to assess how qPCR determinations in wastewater and water samples can be affected by the matrix effect. The results show that the DNA extraction operator did not significantly influence DNA yield. The use of distinct kits resulted in qPCR gene quantifications that did not differ in more than 1 log-unit mL−1. The matrix effect, assessed based on the use of an internal standard, was associated with an underestimation that ranged 0.1–0.9 log gene copy number mL−1 of sample, irrespective of the water type. The reliability on the use of a DNA extraction kit that costs about 3 times less than the most commonly used can be an incentive for the use of DNA based analyses of ARGs in environmental waters. Moreover, the fact that both the DNA extraction operator and the reduced matrix effect have little influence on the final results, are good news, encouraging the compilation of data produced in distinct laboratories. Nevertheless, harmonization efforts are still necessary to minimize bias that may be due associated with other conditions, such as equipment.